Facets of Psychopathy, Intelligence, and Aggressive Antisocial Behaviors in Young Violent Offenders - González Moraga, Fernando Renee; Garcia, Danilo; Billstedt, Eva; Wallinius, Märta (Frontiers in Psychology, 2019)
Psychopathy continues to be a challenge in forensic contexts, and evidence of its association with destructive behaviors, such as aggressive antisocial behaviors, is extensive. However, the potential role of intelligence as moderator of the well-established association between psychopathy and aggressive antisocial behaviors has largely been neglected, despite intelligence having been independently related to both concepts. Increased knowledge of whether intelligence is relevant to this association is needed because of its possible implications on the assessment and treatment of individuals with psychopathic traits and aggressive antisocial behaviors. This study aimed to investigate the association between psychopathic traits, aggressive antisocial behaviors, and intelligence in young violent offenders and to test whether intelligence moderates the relationship between psychopathic traits and aggressive antisocial behaviors. Participants were 269 male violent offenders aged 18 to 25 years, assessed on the Psychopathy Checklist-Revised (PCL-R), the Life History of Aggression (LHA), and the General Ability Index from the Wechsler Adult Intelligence Scale, 3rd edition. Associations were tested with Spearman’s rho and moderation analysis was performed through ordinary least squares regressions. The PCL-R four-facet structure was used for the analyses. We found a positive association between psychopathic traits and aggressive antisocial behaviors, and a small, negative association between the Affective PCL-R facet and intelligence. In the moderation analyses, a small yet statistically significant moderation effect of intelligence on the association between the Interpersonal facet and LHA total scores was demonstrated. However, the amount of variance in the LHA total score explained by the model was very small; 2.9%. We suggest that intelligence, however important for rehabilitation strategies and everyday functioning, is not necessarily pertinent to understanding aggressive antisocial behaviors in young offenders with psychopathic traits.